Developing self-regulation for dietary temptations: intervention effects on physical, self-regulatory and psychological outcomes - McKee, H.; Ntoumanis, Nikos (Springer New York LLC, 2014)
We aimed to investigate whether a self-regulatory skills intervention can improve weight loss-related outcomes. Fifty-five participants (M BMI = 32.60 ± 4.86) were randomized into self-regulation training and advice groups and received two training workshops and weekly practice tasks. The self-regulation training group was trained to use six self-regulatory skills: Delayed gratification, thought control, goal setting, self-monitoring, mindfulness, and coping. The advice group received dietary and physical activity advice for weight loss. Physical, self-regulatory, and psychological measures were taken at baseline, end of intervention (week 8) and at follow-up (week 12). Using intention-to-treat analysis, weight, waist circumference, body fat and body mass index (BMI) were significantly reduced at follow-up for both groups. There were significant increases in all six self-regulatory skills and the psychological measures of self-efficacy, self-regulatory success, and physical self-worth for both groups. Results indicate that self-regulatory skills training might be as effective as dietary and physical activity advice in terms of weight loss and related outcomes.